Modulation of Tumor Microenvironment to Enhance Radiotherapy Efficacy in Esophageal Squamous Cell Carcinoma by Inhibiting Carbonic Anhydrase IX - Xu, Pengqin; Zhang, Yu; Ge, Fanghong; Zhang, Fuming; He, Xia; Gao, Xingya (Frontiers in Oncology, 2021)
The radiotherapy outcomes of patients with advanced esophageal squamous cell carcinoma (ESCC) remain poor due to hypoxia. Carbonic anhydrase IX (CAIX) is a membrane-associated enzyme that induces hypoxia, extracellular acidity, and upregulation of hypoxia-related factors in tumor microenvironment, thereby promoting tumor metastasis. CAIX is upregulated in ESCC tissues compared to normal surrounding tissues. In the current study, we aimed to investigate the effect of CAIX inhibition on the modulation of tumor microenvironment and radiotherapy efficacy in ESCC. Higher CAIX expression was correlated with poorer progression-free survival in ESCC patients. Then, the ethyl N-(4-methylphenyl) sulfonylcarbamate (S4) was used to inhibit CAIX expression in ESCC cells and mice xenografts. The pretreatment of ESCC cells with S4 significantly downregulated CAIX expression, decreased intracellular pH, reduced cell viability, resulting in decreased oxygen consumption and more sensitive response to X-ray irradiation. In mice inoculated with ESCC cells, the combination of X-ray irradiation with S4 further improved survival, delayed tumor growth, decreased hypoxia level, exaggerated DNA damage, and increased apoptosis compared with the groups treated solely with S4 or radiotherapy. In conclusion, our study showed that the inhibition of CAIX by S4 treatment altered hypoxic tumor micro-environment, exaggerated DNA damage, increased apoptosis, and thus enhanced radiotherapy efficacy in ESCC. These findings provided a potential therapeutic strategy for patients with resistant ESCC.